Latex based membrane for oily wastewater filtration: effect of degassing - Ding, Shi Jie (2019)
Graphene oxide (GO) reinforced nitrile butadiene rubber (NBR) membrane was proven to be a promising candidate for oily wastewater treatment in this research. Two samples of latex with the same formulation were prepared via latex compounding and curing method. GO was prepared via exfoliation ahead of latex mixing so as to ensure uniform dispersion in NBR matrix. Fourier-Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD) were adopted to justify the conversion from graphene nanofiber (GNF) to graphite oxide (GtO). Entrapped air was removed from one of the latex samples via vacuum suction. Thus, the degassing effect on membrane performances was investigated. Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) were used to analyse the surface morphologies of the degassed and gassed membranes. SEM revealed the surface features, whereas AFM revealed the surface roughness. By visual inspection of the SEM micrographs, the degassed membrane possessed large pore size while the gassed membrane possessed uniform and small pore size. Both membranes exhibited folded structure but the degassed membrane had a rougher surface. Tensile test was conducted to evaluate the mechanical properties of the membranes. The gassed membrane provided superior E-Modulus and ultimate tensile strength (UTS) of 2.034 and 22.31 MPa, respectively. However, the elongation at break was only 800%. A dead-end membrane test rig was adopted to simulate membrane filtration. When the membranes were subjected to synthetic oily wastewaters of 500 and 1000 ppm diesel oil content, the gassed membrane performed better in terms of oil rejection whereby oil rejection efficiencies above 90% at all pressures and oil concentrations were achieved. Even though the degassed membrane could achieve higher fluxes, its inferior oil rejection efficiency was fatal in practise. The membrane filtration results are in agreement with the surface morphology of the degassed membrane because large pore size allowed oil and water droplets to pass through easily. The permeation flux of the gassed membrane which was 1300 L/m2·hr at 0.5 bar was already promising enough because it exceeded most polymeric membranes performances reported in literature.